Coaching Skill Indicators for Teachers to Empower Student Learning in the 21st Century - Chansiri, Chirawan (Journal of Dhamma for Life, 2025)
Rapid global changes in the 21st century, driven by economic, social, and technological advancements, have significantly influenced educational systems worldwide. In Thailand, despite national efforts to enhance human capital development under the 20-Year National Strategy (2018–2037), the education system continues to face challenges, particularly an overemphasis on rote memorization and content-based assessment. These practices limit students’ opportunities to develop critical thinking, creativity, and lifelong learning skills essential for the 21st century. Consequently, teacher development approaches that effectively promote student-centered learning have become increasingly important. Coaching has emerged as a powerful professional development strategy that focuses on unlocking teachers’ potential, fostering reflective thinking, and promoting sustainable changes in attitudes, cognition, and instructional practices. The purposes of this research were: (1) to identify indicators of coaching skills for teachers that enhance students’ learning in the 21st century, and (2) to examine the congruence and confirm the component structure of these coaching skill indicators. This study employed a quantitative research design. The population consisted of teachers in basic education schools under the Office of the Basic Education Commission, Thailand. The sample was selected using a multistage random sampling technique. The research instrument was a questionnaire measuring teachers’ coaching skills, which was validated for content validity and reliability. Data were analyzed using descriptive statistics and confirmatory factor analysis to verify the construct validity and model fit. The findings revealed that the indicators of teachers’ coaching skills comprised multiple components that demonstrated good congruence with empirical data and met acceptable statistical criteria. The confirmed model indicates that coaching skills are a crucial factor in enhancing students’ learning and competencies required in the 21st century. The results of this study provide empirical evidence that can inform teacher professional development programs and support the improvement of instructional practices aligned with 21st-century educational goals.